Analisis Manajemen Pengelolaan Dana Desa di Desa Jungke Kecamatan Permata Kabupaten Bener Meriah - Irhas Jaya; Humaizi Humaizi; Nurman Achmad (PERSPEKTIF, 2020)
This study aims to determine the Management of Village Fund Management in Jungke Village Permata District Bener Meriah Regency and the factors that influence it to achieve these objectives used qualitative research methods by breaking down the data descriptively. Data collection techniques were carried out by interview, document and archive observation using qualitative descriptive analysis techniques. The results of the study show: First the management stages of Village Fund Management in Jungke Village include Planning and Implementation of Reporting and Accountability Administration. Management of Village Fund Management is carried out by the Government of Jungke Village, Permata District, Bener Meriah Regency, and has followed the technical guidelines that have been regulated in the legislation. But in the process is still not optimal. This can be seen from the process of reporting and accountability that is experiencing delays. For the Reporting Process of Realizing the Use of Village Funds not in accordance with the predetermined schedule, causing delays in disbursing funds for the next stage. Likewise with the Responsibility for the use of village funds so that the community cannot evaluate the results of the work of the village government and the Accountability to the Regional Government which is not carried out in a timely manner. Second: Factors that influence the management of village funds include supporting and inhibiting factors. Supporting factors are community participation, facilities and infrastructure, while the inhibiting factors are human resources, technical guidelines for managing village funds that change every year and communication.